Sleep matters: sleep functioning and course of illness in bipolar disorder. - Gruber, J; Miklowitz, D; Harvey, A; Frank, E; Kupfer, D; Thase, M; Sachs, G; Ketter, T (2011)
BACKGROUND: Few studies have prospectively examined the relationships of sleep with symptoms and functioning in bipolar disorder. METHODS: The present study examined concurrent and prospective associations between total sleep time (TST) and sleep variability (SV) with symptom severity and functioning in a cohort of DSM-IV bipolar patients (N = 468) participating in the National Institute of Mental Health Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD), all of whom were recovered at study entry. RESULTS: Concurrent associations at study entry indicated that shorter TST was associated with increased mania severity, and greater SV was associated with increased mania and depression severity. Mixed-effects regression modeling was used to examine prospective associations in the 196 patients for whom follow-up data were available. Consistent with findings at study entry, shorter TST was associated with increased mania severity, and greater SV was associated with increased mania and depression severity over 12 months. DISCUSSION: These findings highlight the importance of disrupted sleep patterns in the course of bipolar illness.